Coastal clean-up in Southeast Asia: lessons learned, challenges, and future strategies - Purba, Noir P.; Pasaribu, Buntora; Faizal, Ibnu; Martasuganda, Marine K.; Ilmi, Muhammad Hafidz; Febriani, Choerunnisa; Alfarez, Raffy R. (Frontiers in Marine Science, 2023)
The significant accumulation of marine debris on beaches poses a challenge and raises serious concerns to the global environmental sustainability. It has been previously reported that Southeast Asian (SEA) is one of the global hotspots of marine debris contributor to almost 30% of marine debris pollution to the world oceans. This review discusses the challenge and provide the information of mitigation efforts associated with beach clean-up initiatives to combat the marine debris in Southeast Asia. We employ the comprehensive of qualitative data analysis from relevant literature reviews and conducting a structured study specific to the region, therefore, this research highlights the prevalence and characteristics of marine debris that addressed Coastal Cleanup Activities (CCA) in Southeast Asian. Plastic debris remains type of marine debris commonly found across the beaches. Furthermore, Coastal Clean Up (CCU) activities involving local communities have progressively gained prominence in addressing marine debris issues by utilizing educational outreach to raise awareness effectively. Participants in these initiatives include students, tourists, and high school students. The crucial gap of Coastal CCA required the consistent application of scientific methods during beach clean-ups in Southeast Asian. The importance of community involvement, the adoption of scientific methodology, regular clean-up initiatives, and the potential of marine citizen science formulation could potentially contribute in facilitating an effective approach of marine debris management and education in Southeast Asia. Given the substantial component of initiatives, the result of this study proposes the focus on marine citizen science emerges in the future as a potential avenue for educating and engaging the public awareness towards understanding and tackling marine debris accumulation in Southeast Asian beaches.